A hydrogel for adhesion prevention: characterization and efficacy study in a rabbit uterus model - Müller, Sascha A.; Weis, Christine; Odermatt, Erich K.; Knaebel, Hanns-Peter; Wente, Moritz N. (European journal of obstetrics & gynecology and reproductive biology, 2011)
Objective - Postoperative peritoneal adhesions following gynaecological surgery remain a clinically relevant problem. One approach to prevent adhesion formation is to apply physical barriers such as hydrogels. - Study design - A physically crosslinked polyvinyl alcohol and carboxymethylcellulose (PVA/CMC) hydrogel (A-Part) was characterized in vitro. Three different traumatization methods were evaluated in a rabbit uterine study. To determine its anti-adhesion efficacy, the hydrogel was first tested in an in vivo pilot study and then in a larger trial to compare it with icodextrin 4% solution (Adept®) and controls. - Results - Rheological measurements showed an increased elasticity of the hydrogel after freezing. In vivo experiments revealed a clear reduction in incidence, extent and severity of adhesions compared to the icodextrin 4% solution and the untreated control group. - Conclusions - These results warrant further investigation of the PVA/CMC A-Part hydrogel in clinical trials focused on gynaecological procedures.
First published online: 10 December 2010
Gesehen am14.09.2022